Application of mind-body therapies on anxiety and quality of life in patients undergoing hemodialysis: A systematic review - Wita Handayani; Krisna Yetti; Masfuri Masfuri; Sri Yona (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Chronic kidney disease is one of the global public health challenges that continues to increase with a significant impact on morbidity, mortality and high health care costs. Hemodialysis, one of the renal replacement therapy methods, often causes anxiety and decreased quality of life. Mind body therapies such as guided imagery, yoga and meditation have the potential to reduce anxiety and improve the quality of life of patients undergoing hemodialysis. Purpose: To evaluate the effectiveness application of mind body therapies on anxiety and quality of life in patients undergoing hemodialysis. Method: This systematic review uses an approach that follows the PRISMA guidelines. Searches were conducted in six electronic databases, namely Scopus, Springerlink, Proquest, EBSCO, Science Direct and Pubmed with appropriate keywords. The included articles were published within the last 10 years, in English and the type of research was RCT or quasi-experimental. After the selection process, 10 articles met the criteria for further analysis. Results: Eight articles were RCT designs and two articles were quasi-experimental designs. The application of mind body therapies including guided imagery, yoga and meditation is a complementary therapy that can reduce anxiety and improve quality of life. In addition, it also affects the improvement of sleep quality, reduces depression, reduces stress levels and emotional regulation in patients undergoing hemodialysis. Conclusion: Mind body therapies have been proven effective in reducing anxiety and improving the quality of life of hemodialysis patients. This therapy can be used both during hemodialysis sessions and when done alone at home. With its various benefits, this therapy has the potential to be integrated into holistic and evidence-based patient care.